Differential Expression of miR-21-5p, miR-20a-5p, TGF-β1, and TGF-β Receptor 2 in Skin, Serum, and Lung Samples Exposed to Sulfur Mustard - Mohadeseh Valizadeh; Shiva Irani; Mahmood Tavallaei; Masoud Soleimani (Iranian Journal of Allergy, Asthma and Immunology, 2023)
Sulfur mustard (SM) or mustard gas is a blister chemical agent that causes pulmonary damage by triggering inflammation and oxidative injury. Alterations in microRNA (miR) transcript levels are found in pulmonary diseases and even inflammation. Therefore, we evaluated the expression levels of miR-20a-5p, miR-21-5p, and two target transcripts (transforming growth factor-beta [TGF-β1] and TGF-β receptor 2 [TGFR2]) in lung, serum, and skin samples from patients exposed to SM. Total RNA was extracted from lung, serum, and skin samples of patients with moderate (n=10) and high (n=10) SM exposure, as well as 10 healthy subjects. Following the synthesis of complementary deoxyribonucleic acid using real-time polymerase chain reaction, we determined the expression levels of miR-20a-5p, miR-21-5p, TGF-β1, and TGFR2 transcripts. Furthermore, we evaluated the sensitivity and specificity of the chosen miRs by employing receiver operating characteristic (ROC) curves and calculating the area under the ROC curve. The results showed that miR-20a-5p and miR-21-5p expressions in the groups with moderate and high SM exposure were significantly lower than the normal controls. The expression analysis demonstrated that TGFR2 was significantly less expressed in skin samples exposed to SM in both groups of patients compared with healthy controls. Furthermore, the TGF-β1 expression in the skin samples of the group with moderate SM exposure was lower than that of the normal control group. Our findings suggest that miR-20a-5p, miR-21-5p, TGF-β1, and TGFR2 expressions could be used as potential biomarkers for discriminating SM-exposed patients from healthy individuals.